Diagnosis dan Tata Laksana Urtikaria Kronik: Tinjauan Pustaka - Retno Eka Sari; Raveinal (Cermin Dunia Kedokteran, 2026)
Chronic urticaria is an inflammatory skin condition characterized by urticarial skin lesions, angioedema, or both, occurring continuously or sporadically for 6 weeks or more, and may be spontaneous or induced by specific factors. The impact of chronic urticaria significantlyincludes physical discomfort as well as mental health disturbances (particularly anxiety and depression), sexual dysfunction, impaired interpersonal relationships, and limitations in daily activities including work and school. Diagnosis is established based on clinical historyand physical examination, with additional investigations performed in selected cases to exclude secondary causes. Management includes antihistamines as first-line therapy, with treatment escalation based on patient response. This individualized therapeutic approach follows a step-up or step-down principle based on the level of disease control. The treatment target is disease remission, indicated by a sustained urticaria activity score (UAS) of 0, controlled disease with a urticaria control test (UCT) score of 16, and normalization of quality of life. A good understanding of this condition along with proper patient education is essential to help control symptoms and improve overall quality of life.